Heat transfer performance investigation of a water cooled chiller operated with nanofluid / Letchumanan Lakshmanan - Letchumanan, Lakshmanan (2012)
Nanofluid is the suspension of nanoparticles in a base fluid. Nanofluids are promising fluids for heat transfer enhancement due to their anomalously high thermal conductivity. At present, there is a significant discrepancy in nanofluid thermal conductivity data obtained from various experimental models & researches conducted. In the first part of this research report, a detailed study on nanofluid had been discussed and found that three properties of nanofluid are being a promising coolant which are increased thermal conductivity, increased single phase heat transfer and its stability. Types of nanofluid that possibly be used as coolant for water chillers, properties of nanofluid and how it could improve in enhancement of heat transfer of water chillers using nanofluid had been discussed. Moreover, characteristics of nanofluid for the improvement of heat transfer rate due to the effect of some parameters such as particle size and shape, particle materials, and temperature on the thermal conductivity models are also explained. Mechanism of thermal conductivity of nanofluid, challenges and future development of nanofluid was also included in this study. In the second part, studies on what is chiller, types of chillers, detail explanation of water chillers and its working principle had been performed. Adding on, the purpose of cooling system for water chillers, types of coolant used for heat transfer purposes, and advantages of using nanofluid in water chiller had been explained. In the final part of this study, a comparison calculation had been performed for heat transfer performance investigation of water chiller using water and two different types of nanoparticles which is Al2O3 & TiO2, which are used as coolant for water chillers in this research report. It was observed that the highest heat transfer rate achieved using Al2O3 nanofluid was 29,128.62 W with 5.0 m/s inlet velocity by 0.5% particle volume fraction, followed by TiO2 nanofluid 29,126.19 W with 0.5% particle volume fraction at 5m/s inlet velocity, and finally using pure water in water chiller with 26,661.18 W at 5.0m/s inlet velocity.